Access to Finance, Financial Development and Firm Ability to Export: Experience from Asia–Pacific Countries. Issue 1 (25th March 2018) - Kumarasamy, Durairaj; Singh, Prakash
Abstract : With particular reference to Asia–Pacific countries, the present study examines how access to finance and financial development affects firms' ability to enter export markets. Using firm‐level data from the World Bank Enterprises Survey, we found that access to finance plays a significant role in improving firms' ability to export. In addition, development of the financial sector fosters export market entry. Among the financial development indicators, reach of the banking sector variable is most prominent. The present study suggests that improvements in access to finance and financial development (increases in the reach of the banking sector) enable firms operating away from capital or major cities to enter export markets easily. The present study supports policy intervention to strengthen access to the financial sector, which would encourage firms to export, and to facilitate export market entry for remotely located firms.